Old Black Witch! - Devlin, Wende; Devlin, Harry (Chicago, Parents' Magazine Press, 1963)
At first Nicky's and his mother's efforts to turn an old New England house into a tearoom are hampered by an old black witch who haunts the place; then, they find out she can cook.
Keywords: Witches -- Fiction